Case Report: Combined Liver-Kidney Transplantation to Correct a Mutation in Complement Factor B in an Atypical Hemolytic Uremic Syndrome Patient - López-Trascasa, Margarita; Alonso-Melgar, Ángel; Melgosa-Hijosa, Marta; Espinosa-Román, Laura; Lledín-Barbancho, María Dolores; García-Fernández, Eugenia; Rodríguez de Córdoba, Santiago; Sánchez-Corral, Pilar (Frontiers in Immunology, 2021)
Pathogenic gain-of-function variants in complement Factor B were identified as causative of atypical Haemolytic Uremic syndrome (aHUS). These mutations generate a reduction on the plasma levels of complement C3. A four-month-old boy was diagnosed of hypocomplementemic aHUS on May 2000, and during the following three years he suffered seven recurrences. He developed a severe hypertension which required 6 anti-hypertensive drugs and presented acrocyanosis and several confusional episodes. Plasma infusion or exchange, and immunosuppressive treatments did not improve the clinical evolution, and the patient developed end-stage renal disease at the age of 3 years. Hypertension and vascular symptoms persisted while he was on peritoneal dialysis or hemodialysis, as well as after bilateral nephrectomy. C3 levels remained low, while C4 levels were normal. The patient presented a heterozygous gain-of-function mutation in Factor B (K323E). A combined liver and kidney transplantation (CLKT) was performed on March 2009. Kidney and liver functions normalized in the first two weeks and the C3/C4 ratio immediately after transplantation, indicating that the C3 activation has been corrected. After remaining stable for 4 years, the patient suffered a B-cell non-Hodgkin lymphoma that was cured by chemotherapy and reduction of immunosuppressive drugs. Signs of liver rejection with cholangitis were observed a few months later, and a second liver graft was done 11 years after the CLKT. One year later, the patient maintains normal kidney and liver functions, also C3 and C4 levels were within the normal range. The 12-year follow-up of the patient reveals that, in spite of severe complications, CLKT was an acceptable therapeutic option for this aHUS patient.